SAT0270 Ultrasonography of major salivary glands in juvenile sjÖgren's syndrome – preliminary findings in a multi-center study. (15th June 2017) - Hammenfors, DS; Valim, V; Bica, B; Pasoto, SG; Lilleby, V; Nieto-González, JC; Silva, CA; Mossel, E; Pereira, RM; Bootsma, H; Brun, JG; Jonsson, R; et al.
Abstract : Background: Juvenile Sjögren's syndrome (jSS) is a rare, poorly defined and possibly underdiagnosed condition. There is little information on the use of major salivary gland ultrasonography (SGUS) in this patient-group. Objectives: To characterize symptoms and clinical findings of jSS and to investigate SGUS as a diagnostic tool. Methods: Sixty-four patients were recruited from Brazil (n=40), Norway (n=11), the Netherlands (n=8) and Spain (n=5). All patients had disease onset at the age of 18 or younger. Clinical examination and sialometry was performed in 60/64 patients. Additional clinical information was obtained from the medical records and through patient interview. SGUS of the parotid and submandibular glands was performed in all patients using linear high-frequency transducers (6–15 MHz), by an expert in SGUS. Glandular homogeneity and presence of hypoechogenic areas were evaluated and glands characterized as normal or SS-like. Results: The female:male ratio was 6:1. Mean age at diagnosis was 12.1 years (range 4–18), with first symptoms occurring at 10.3 years (range 1–17). Time from onset of symptoms until diagnosis was 1.6 years (range -2–8 years). Subjective oral and ocular symptoms were reported in 70% and 64% patients, respectively. Reduced secretion of tears was detected in 41% patients, and hyposalivation in 31% patients. Minor salivary gland lip biopsy had been performed and focus score determined in 34 patients; 28 biopsies (82%) had focus score ≥1. Serologically, 92% were positive for ANA, 73% were anti-Ro/SSA+, 38% were anti-La/SSB+, and 41% were RF+. Salivary gland enlargement had been experienced by 53% of the patients; one patient had also experienced lacrimal gland enlargement. Systemic manifestations at some time-point, was registered in 66% of the patients. Systemic treatment at inclusion was registered in 67% of the patients; previous systemic treatment was registered in 83%. Diagnostic criteria for primary Sjögren's syndrome (pSS) was fulfilled by 34/64 patients (53%) and 39/64 patients (61%), AECG criteria and ACR/EULAR criteria, respectively. SGUS revealed SS-like changes in 37/64 patients (59%); interestingly, SS-like findings were observed in 22/23 patients in the European cohort, compared to 15/40 patients in the Brazilian cohort. Conclusions: Common symptoms and findings in jSS include dry mouth, systemic manifestations and salivary gland enlargement, followed by reduced tear secretion and hyposalivation. Disclosure of Interest: None declared